Social appearances : a philosophy of display and prestige - Carnevali, Barbara (Columbia themes in philosophy, social criticism, and the arts., 2020)
Philosophers have long distinguished between appearance and reality, and the opposition between a supposedly deceptive surface and a more profound truth is deeply rooted in Western culture. At a time of obsession with self-representation, when politics is enmeshed with spectacle and social and economic forces are intensely aestheticized, philosophy remains moored in traditional dichotomies: being versus appearing, interiority versus exteriority, authenticity versus alienation. Might there be more to appearance than meets the eye 'In this strikingly original book, Barbara Carnevali offers a philosophical examination of the roles that appearances play in social life. While Western metaphysics and morals have predominantly disdained appearances and expelled them from their domain, Carnevali invites us to look at society, ancient to contemporary, as an aesthetic phenomenon. The ways in which we appear in public and the impressions we make in terms of images, sounds, smells, and sensations are discerned by other people's senses and assessed according to their taste; this helps shape our ways of being and the world around us. Carnevali shows that an understanding of appearances is necessary to grasp the dynamics of interaction, recognition, and power in which we live' and to avoid being dominated by them. Anchored in philosophy and traversing sociology, art history, literature, and popular culture, Social Appearances develops new theoretical and conceptual tools for today's most urgent critical tasks.